Summary of schemes for the assistance of the unemployable blind (1930)
1930 1930 1930s 6 pages 2. Monmouthshire. Grants not exceeding 12/6 a week to bring income of single blind persons up to 20/- a week and married blind persons up to 30/- a week. Destitute cases dealt with by Boards of Guardians. Northumberland. Augmented to 18/- a week. Not eligible (1) married women living with sighted husbands. (2) Persons under 21 years of age living with parents. (3) Mendicants. Nottinghamshire. Augmented to 15/- a week. Not eligible - (a) persons in receipt of Poor Law Relief. (b) persons refusing visitation and information as to means. Pecuniary assistance not exceeding 5/- a week from relatives or friends not calculated. Fixed value of 5/- a week placed on board-lodgings received by a single person living with relatives for which no payment is made. Oxfordshire. Cases considered on their merits. Generally augmented to 15/- a week persons living alone. Augmented to 20/-a week, a person living with another (not blind) Augmented to 10/- a week where more than two persons living in the family. Payments sometimes made in respect of assistance or attendance in their home. BOROUGH COUNCILS. Etc. Bath. Augmented to £1 a week. Birkenhead. Augmented to 27/6 a week - persons over 21 years of age. Augmented to £2 2/- man and wife, both blind. (Persons under 21 years of age assisted as considered desirable). Must be British subjects for at least 10 years. Must be resident in the Borough for at least 3 years. If persons come to reside in the borough from an area in which augmentation of income is given, grant not exceeding same rate awarded until 3 years residence has been completed. If satisfied that a person is genuinely resident grant may be given to avoid hardship, even though stipulated period is not completed. In calculating means, the method of assessment under the O.A.P. Acts adopted. Sick-pay, amount received as sickness benefit during period of not more than 3 months calculated. Not eligible Persons in receipt of Poor Law Relief (except medical treatment). 292/841.4/1/40